Extracellular Vesicle lncRNA Metastasis-Associated Lung Adenocarcinoma Transcript 1 Released From Glioma Stem Cells Modulates the Inflammatory Response of Microglia After Lipopolysaccharide Stimulation Through Regulating miR-129-5p/High Mobility Group Box-1 Protein Axis - Yang, Jiankai; Sun, Guozhu; Hu, Yuhua; Yang, Jipeng; Shi, Yijun; Liu, Hongjiang; Li, Chen; Wang, Yuanyu; Lv, Zhongqiang; Niu, Jianxing; Liu, Honglei; Shi, Xuefang; et al. (Frontiers in Immunology, 2020)
Glioma stem cell (GSC)–derived extracellular vesicles (EVs) can mediate the communication between GSCs and microglia. Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) expression in GSCs, EVs, and supernatant was detected by real-time PCR. The direct targeting between MALAT1 and miR-129-5p, miR-129-5p, and HMGB1 were tested with luciferase reporter analysis. The expression and secretion of interleukin (IL)-6, IL-8, and tumor necrosis factor (TNF)-α were determined in lipopolysaccharide-stimulated microglia or miR-129-5p inhibitor transferred to microglia exposed to GSC EVs or EVs derived from siMALAT1 pre-transferred GSCs. MALAT1 was enriched in GSC EVs compared with GSCs, and up-regulated MALAT1 was also observed in microglia upon GSC EVs incubation. The relative expression and secretion of IL-6, IL-8, and TNF-α in lipopolysaccharide-stimulated microglia were up-regulated in the GSC supernatant group, which could be reversed by dimethyl amiloride (DMA) (EV secretion inhibitor) co-administration or si-MALAT1 pre-transfection of GSCs. Luciferase reporter assay testified the direct binding of MALAT1 and miR-129-5p, miR-129-5p, and HMGB1, and si-MALAT1 could up-regulate miR-129-5p expression and down-regulate HMGB1 expression in microglia cells. The concentration of IL-6, IL-8, and TNF-α in lipopolysaccharide-stimulated microglia exposed to EVs from siMALAT1 transfected GSCs could be up-regulated by miR-129-5p inhibition. EVs lncRNA MALAT1 released from GSCs could modulate the inflammatory response of microglia after lipopolysaccharide stimulation through regulating the miR-129-5p/HMGB1 axis.